Sosialisasi Pemanfaatan Aplikasi JKN Mobile untuk skrining Riwayat Kesehatan : Penyakit Tidak Menular (PTM) - Maulidta Karunianingtyas Wirawati; Sigit Sugiharto; Harsono Harsono (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Non-Communicable Diseases (NCDs) are a group of diseases that are not transmitted through infection or direct contact with other individuals, but are caused by a combination of genetic, environmental and behavioral factors. NCDs are one of the main causes of death globally, with prevalence rates continuing to increase, especially in developing countries. The main risk factors for NCDs include unhealthy diet, lack of physical activity, tobacco consumption and excessive alcohol use. Prevention and control of NCDs requires a multidisciplinary approach, involving public education, health system strengthening, public policies that support health, as well as early detection and risk management. Effective treatment of NCDs is very important to improve people's quality of life and reduce the economic burden caused by this disease. Prevention of PTM can be done through PTM screening. The government has provided this skinning method through the JKN mobile application. The method used in this activity is direct socialization and discussion directly with participants using power point media. The results showed that participants were very enthusiastic about following the education provided and enthusiastic about knowing how to carry out screening using the JKN application.